Literasi Keuangan Terhadap Pengelolaan Keuangan Pekerja Generasi Mileneal Di KantorJasa Konstruksi Kota Makasaar - Hermin Andi Magga; Roswiyanti Roswiyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Aims to determine the effect of financial literacy (X) on the financial management of millennial generation workers (Y) at the Makassar city Construction Services Office using descriptive quantitative methods. The source of the data used is primary data obtained through a questionnaire with a population of respondents, namely millennial generation workers at the Makassar city Construction Services Office. While secondary data is from previous research journals. Data analysis used is hypothesis testing, correlation test and simple linear regression test using SPSS. The results of the study show that the financial literacy variable has no effect on the financial management of millennial generation workers.